Exploiting off-target effects of estrogen deprivation to sensitize estrogen receptor negative breast cancer to immune killing. Issue 7 (8th July 2021) - Wolfson, Benjamin; Padget, Michelle R; Schlom, Jeffrey; Hodge, James W
Abstract : Background: There are highly effective treatment strategies for estrogen receptor (ER)+, progesterone receptor (PR)+, and HER2+ breast cancers; however, there are limited targeted therapeutic strategies for the 10%–15% of women who are diagnosed with triple-negative breast cancer. Here, we hypothesize that ER targeting drugs induce phenotypic changes to sensitize breast tumor cells to immune-mediated killing regardless of their ER status. Methods: Real-time cell analysis, flow cytometry, qRT-PCR, western blotting, and multiplexed RNA profiling were performed to characterize ER+ and ER− breast cancer cells and to interrogate the phenotypic effects of ER targeting drugs. Sensitization of breast cancer cells to immune cell killing by the tamoxifen metabolite 4-hydroxytamoxifen (4-OHT) and fulvestrant was determined through in vitro health-donor natural killer cell 111 IN-release killing assays. A syngeneic tumor study was performed to validate these findings in vivo. Results: Pretreatment with tamoxifen metabolite 4-OHT or fulvestrant resulted in increased natural killer (NK)–mediated cell lysis of both ER+ and ER− breast cancer cells. Through multiplexed RNA profiling analysis of 4-OHT-treated ER+ and ER− cells, we identified increased activation of apoptotic and death receptor signaling pathways and identified G protein-coupled receptor for estrogen (GPR30) engagement as a putative mechanism for immunogenic modulation. Using the specific GPR30 agonist G-1, we demonstrate that targeted activation of GPR30 signaling resulted in increased NK cell killing. Furthermore, we show that knockdown of GPR30 inhibited 4-OHT and fulvestrant mediated increases to NK cell killing, demonstrating this is dependent on GPR30 expression. Moreover, we demonstrate that this mechanism remains active in a 4-OHT-resistant MCF7 cell line, showing that even in patient populations with ER+ tumors that are resistant to the cytotoxic effects of tamoxifen, 4-OHT treatment sensitizes them to immune-mediated killing. Moreover, we find that fulvestrant pretreatment of tumor cells synergizes with the IL-15 superagonist N-803 treatment of NK cells and sensitizes tumor cells to killing by programmed death-ligand 1 (PD-L1) targeting high-affinity natural killer (t-haNK) cells. Finally, we demonstrate that the combination of fulvestrant and N-803 is effective in triple-negative breast cancer in vivo. Conclusion: Together, these findings demonstrate a novel effect of ER targeting drugs on the interaction of ER+ and, surprisingly, ER− tumors cells with the immune system. This study is the first to demonstrate the potential use of ER targeting drugs as immunomodulatory agents in an ER agnostic manner and may inform novel immunotherapy strategies in breast cancer.